THE ROLE OF ISLAMIC FEMINISM IN ADDRESSING GENDER INEQUALITY IN MUSLIM SOCIETIES - Cholid Fadil; Saifuddin Zuhri (Penelitian dan Pengembangan Ilmu, 2025)
Gender inequality in Muslim societies is often influenced by traditional interpretations of Islamic texts, resulting in the marginalization of women. This research aims to explore the role of Islamic feminism in opposing and reformulating these interpretations to achieve gender justice. This study aims to analyze how Islamic feminism can interpret religious texts to overcome gender inequality in the context of contemporary Muslim society. This research uses a Systematic Literature Review (SLR) approach by collecting and analyzing 24 peer-reviewed articles from various academic sources. Data was collected through Scopus, Web of Science, and Springer databases, and analyzed using thematic analysis methods. The main findings show that Islamic feminism offers a contextual hermeneutic approach that emphasizes the importance of women's experiences and justice in the interpretation of texts. This has the potential to change the patriarchal narrative that has dominated understanding of Islam. This research makes a significant contribution to the development of more inclusive Islamic feminist theory and religious practice, as well as paving the way for more equitable social reform in Muslim societies.